2015
DOI: 10.1093/molbev/msv059
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Description of a Protein Fitness Landscape Based on Molecular Features

Abstract: Understanding the driving forces behind protein evolution requires the ability to correlate the molecular impact of mutations with organismal fitness. To address this issue, we employ here metallo-β-lactamases as a model system, which are Zn(II) dependent enzymes that mediate antibiotic resistance. We present a study of all the possible evolutionary pathways leading to a metallo-β-lactamase variant optimized by directed evolution. By studying the activity, stability and Zn(II) binding capabilities of all mutan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
70
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(77 citation statements)
references
References 63 publications
6
70
0
Order By: Relevance
“…Hydrophobic side chains such as F114 or F230 were not identified as residues that may play an important role in substrate recognition from a structural analysis but from an in vitro evolution experiment. The identification of several relevant hydrophobic residues in substrate interactions (in particular F114, F119 and F230) is in agreement with similar observations reported for the B1-type MBLs BcII, SPM-1 and IMP, where residues G262 (BcII and SPM-1) and V67 (IMP) play essential roles in substrate recognition253043. While the structural origins for the contributions of these hydrophobic residues to substrate binding and hydrolysis remain to be elucidated their identification indicates that MBLs have a diverse array of possibilities to adapt to new selection pressures, thus compounding their threat to health care.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Hydrophobic side chains such as F114 or F230 were not identified as residues that may play an important role in substrate recognition from a structural analysis but from an in vitro evolution experiment. The identification of several relevant hydrophobic residues in substrate interactions (in particular F114, F119 and F230) is in agreement with similar observations reported for the B1-type MBLs BcII, SPM-1 and IMP, where residues G262 (BcII and SPM-1) and V67 (IMP) play essential roles in substrate recognition253043. While the structural origins for the contributions of these hydrophobic residues to substrate binding and hydrolysis remain to be elucidated their identification indicates that MBLs have a diverse array of possibilities to adapt to new selection pressures, thus compounding their threat to health care.…”
Section: Discussionsupporting
confidence: 90%
“…This hypothesis is supported by the observation that both the evolved variant #5–19 and in particular the engineered mutant F119M have enhanced k cat values towards some or all of the substrates when compared to the other variants and the wild-type enzyme, but their MIC values are not better than those of variants #5–1, #5–2 and #5–3. This observed discrepancy in the enhancement of MIC values and catalytic efficiency may be due to impaired metal ion binding of the two mutants when compared to the wild-type enzymes and variants #5–1–#5–3, as was observed for some mutants of the B1-type MBL BcII30. However, it appears more likely that due to the significantly increased K m for cefoxitin both the F119M mutant and #5–19 variant operate at sub-saturated levels in the in vivo assays.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…Such model proteins include TEM‐1 β‐lactamase, dihydrofolate reductase, and adenylate kinase (Wang et al , 2002; Couñago et al , 2006; Weinreich et al , 2006; Peña et al , 2010; Jacquier et al , 2013; Rodrigues et al , 2016). These advances have provided a greater understanding into how the physicochemical properties of a protein relate to fitness and allow investigators to explore the role of fitness landscapes in adaptive evolution (Weinreich et al , 2006; Dean & Thornton, 2007; Walkiewicz et al , 2012; Harms & Thornton, 2013; Meini et al , 2015; Palmer et al , 2015). …”
Section: Introductionmentioning
confidence: 99%
“…Because NDMs are Zn(II)-dependent enzymes, it has been suggested that the deficits of this cation in commercial media could be responsible for these false-negative results (4). Indeed, Zn(II) availability has been shown to be crucial for bacterial fitness when resistance to antibiotics depends on class B enzymes (8). However, supplementation of culture media with up to 100 g/ml zinc sulfate failed to reverse these false-negative results (4,9), suggesting the presence of other mechanisms responsible for this deficient performance.…”
mentioning
confidence: 99%